2018
DOI: 10.1016/j.jana.2017.06.006
|View full text |Cite
|
Sign up to set email alerts
|

A Multicomponent Approach to Evaluating a Pre-exposure Prophylaxis (PrEP) Implementation Program in Five Agencies in New York

Abstract: Research has shown that pre-exposure prophylaxis (PrEP) is effective for preventing HIV infection. We developed the Targeted PrEP Implementation Program (TPIP), an 18-month project that involved five statewide agencies, to assess the extent to which PrEP could be implemented in "real world" clinical settings. The target population was men who have sex with men at high risk for HIV infection. Data were collected from a variety of sources. Implementing PrEP statewide required facilitating provider capacity, deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(47 citation statements)
references
References 5 publications
0
47
0
Order By: Relevance
“…This model has been shown to improve health care entities' ability to identify, recruit, and retain patients. 18 However, information and outreach must align with the unique needs of the intended patient. Studies looking into PrEP awareness in transgender populations find the absence of transinclusive educational and marketing PrEP materials to be a significant barrier to knowledge and access.…”
Section: Lack Of Awareness or Insufficient Knowledge About Prepmentioning
confidence: 99%
“…This model has been shown to improve health care entities' ability to identify, recruit, and retain patients. 18 However, information and outreach must align with the unique needs of the intended patient. Studies looking into PrEP awareness in transgender populations find the absence of transinclusive educational and marketing PrEP materials to be a significant barrier to knowledge and access.…”
Section: Lack Of Awareness or Insufficient Knowledge About Prepmentioning
confidence: 99%
“…Doblecki-Lewis [67] and Hoffman et al [55] offered a unified approach, urging services to consider 'task-shifting' between primary care staff and HIV specialists. Alternatively, seven studies identified the potential role for 'PrEP navigators'-individuals performing activities to assist potential and current PrEP users through bridging communications with relevant services through information provision and support [62,[68][69][70][71][72][73]. Additional training for service providers was noted as a necessity by 18 studies to ensure effective and sustainable PrEP delivery and programming, which could also provide a solution to bridging the gap between service provider knowledge and the prescribing of PrEP [55,57,59,60,63,65,[67][68][69][72][73][74][75][76][77][78][79][80][81].…”
Section: Theme One: Prep Service Aspects Settings and Staffmentioning
confidence: 99%
“…Disruption in routine was also reported [54,93,103,108] but Vaccher et al [103] stated that this could be reduced by carrying spare medication for emergencies. Certain service user groups were identified as being at risk of low PrEP adherence, including those from ethnic minorities, [73,91,111] young MSM, [91] smokers, [111] and those with problematic alcohol or substance use, [91] all of which are exacerbated by systemic disadvantages within society or from an individual's predisposition to risky behaviour.…”
Section: Theme Three: Prep Adherence Within Formal Service Structuresmentioning
confidence: 99%
See 1 more Smart Citation
“…There are several potential sources for financial assistance for these additional costs. Some states have developed PrEP assistance programs to assist with these costs for those at risk for HIV acquisition [105]. Both insurance plans and patient assistance programs including those sponsored by pharmaceutical companies should also be approached to include provisions that ensure basic lab services and follow-up visits will be covered, as continued costs for these services serve as a deterrent for YBMSM to stay engaged in care and adherent to medications.…”
Section: Address Structural and Policy Barriers To Prep Care Modalitiesmentioning
confidence: 99%